Almanac 2015: coronary artery disease - D. Shavelle (Кардіохірургія та інтервенційна кардіологія)
Recent years have seen major advances in the evaluation and treatment of patients with coronary artery disease. These include assessment of novel biomarkers and imaging methods for patients at risk for coronary artery disease, care of patients with ST-segment elevation myocardial infarction, a novel device to treat medical refractory angina, use of non-statin lipid-lowering agents, a better understanding of the risks and benefits of longterm dual antiplatelet therapy and the use of the newer antiplatelet agents. This article summarises research related to coronary artery disease published in Heart in 2014 and 2015, within the context of other major cardiovascular journals.